Implementation of the Wavelet Transformation Algorithm for the Recognition and Recitation of the Qur'anic Verses Through Voice - Bustami Bustami; Sayed Fachrurrazi; Fahrul Rozi Siregar (TECHSI - Jurnal Teknik Informatika, 2019)
The advancement of computer technology not only makes it easy for humans to carry out activities. One of the human intelligences planted into computer technology is recognizing the Qur'anic verses in Surah Ar-Rahman. Wafelet transformation method is one method for sound recognition, this system recognizes the verses of Al-Qur'an Surah Ar-Rahman from recorded sound files with the .wav file extension and built using the Delphi programming language.